Cardiomyocyte-specific loss of plasma membrane calcium ATPase 1 impacts cardiac rhythm and is associated with ventricular repolarisation dysfunction. (November 2022) - Wilson, Claire; Stafford, Nicholas; Zi, Min; Chelu, Alexandru; Niort, Barbara C.; Li, Yatong; Baudoin, Florence; Prehar, Sukhpal; Trafford, Andrew W.; Cartwright, Elizabeth J.
Abstract: Plasma membrane calcium ATPase 1 (PMCA1, Atp2b1 ) is emerging as a key contributor to cardiac physiology, involved in calcium handling and myocardial signalling. In addition, genome wide association studies have associated PMCA1 in several areas of cardiovascular disease including hypertension and myocardial infarction. Here, we investigated the role of PMCA1 in basal cardiac function and heart rhythm stability. Cardiac structure, heart rhythm and arrhythmia susceptibility were assessed in a cardiomyocyte-specific PMCA1 deletion (PMCA1 CKO ) mouse model. PMCA1 CKO mice developed abnormal heart rhythms related to ventricular repolarisation dysfunction and displayed an increased susceptibility to ventricular arrhythmias. We further assessed the levels of cardiac ion channels using qPCR and found a downregulation of the voltage-dependent potassium channels, Kv 4.2, with a corresponding reduction in the transient outward potassium current which underlies ventricular repolarisation in the murine heart. The changes in heart rhythm were found to occur in the absence of any structural cardiomyopathy. To further assess the molecular changes occurring in PMCA1 CKO hearts, we performed proteomic analysis. Functional characterisation of differentially expressed proteins suggested changes in pathways related to metabolism, protein-binding, and pathways associated cardiac function including β-adrenergic signalling. Together, these data suggest an important role for PMCA1 in basal cardiac function in relation to heart rhythm control, with reduced cardiac PMCA1 expression resulting in an increased risk of arrhythmia development. Graphical abstract: Unlabelled Image Highlights: PMCA1 is important in maintaining normal cardiac rhythms Loss of PMCA1 in cardiomyocytes increases susceptibility to ventricular arrhythmias PMCA1 cardiomyocyte-deletion impacts signalling pathways associated with cardiac rhythm